In-Service Capacity Building of Teachers - Dewan, Hriday Kant (Voices of Teachers and Teacher Educators, 2018)
The paper considers the machanism for In-Service Capacity Building of Teachers and points out the need for systems that have participation of teachers with a sense for their need, choice and purpose. It suggests that mechanism for large scale traning through cascade needs to be reimagined as different from replication of the previous stage of the cascade in a manner that the participant teachers feel respected, stimulated and excited about work.